2011
DOI: 10.4269/ajtmh.2011.10-0695
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Virulence-Associated Plasmids in Rhodococcus equi in Humans with and without Acquired Immunodeficiency Syndrome in Brazil

Abstract: Virulence of Rhodococcus equi strains from 20 humans in Brazil was investigated by using a polymerase chain reaction to characterize isolates as virulent (VapA), intermediately virulent (VapB), and avirulent. Nine isolates were obtained from human immunodeficiency virus (HIV)–positive patients, six from HIV-negative patients, and five from patients of unknown status. Five isolates were VapB positive, four were VapA positive, and eleven were avirulent. Among the nine isolates from HIV-positive patients, five co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…We assessed selected epidemiological and clinical data from the records of the human patients (gender, age, history of contact with domestic animals and/or livestock farms), major clinical signs, underlying conditions, clinical specimens and laboratory diagnoses. The diagnosis of HIV/AIDS was defined as the presence of antibodies against HIV in serum samples (Ribeiro, Takai et al., ; Takai et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed selected epidemiological and clinical data from the records of the human patients (gender, age, history of contact with domestic animals and/or livestock farms), major clinical signs, underlying conditions, clinical specimens and laboratory diagnoses. The diagnosis of HIV/AIDS was defined as the presence of antibodies against HIV in serum samples (Ribeiro, Takai et al., ; Takai et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of human infections has increased globally, and rhodococcosis represents an emerging risk in coming years (Shahani, ). Rhodococcus equi typically causes pyogranulomatous bronchopneumonia and occasionally extrapulmonary infections in both immunosuppressed and immunocompetent patients (Takai et al., ), particularly people living with HIV/AIDS (Ribeiro, Takai et al., ) and transplant recipients (Vergidis et al., ). In turn, sources of infection and routes of transmission of the pathogen to humans remain poorly understood, although inhalation, and history of contact with livestock and environment of farms are considered to be risk factors (Meijer & Prescott, ; Prescott, ; Vázquez‐Boland et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a Brazilian study of the virulence genes and plasmid profiles of the R. equi isolates from the lymph nodes of slaughtered wild boar found that 63.2% of the isolates contained the vapB gene, and the majority was identified as carrying type 8 plasmids [8]. Interestingly, this same plasmid profile (VapB type 8) is the one most frequently found in HIV-positive patients in Brazil [25], suggesting the zoonotic potential of R. equi isolates from wild boar. However, the human with rhodococcosis generally have no history of contact with pigs, wild boar or the environments of these species [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the human with rhodococcosis generally have no history of contact with pigs, wild boar or the environments of these species [25]. It is possible that the consumption of undercooked pig and wild boar products may be a route of infection with R. equi in humans in some countries [6,8,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Expression of VapA was found to be dependent on both temperature and pH (192, 193), a feature shared with proteins encoded by virulence plasmids of Yersinia pestis and Shigella flexneri (194–196). VapB is encoded by a separate plasmid from the one encoding VapA (197, 198), and is associated with less virulent R. equi infections in humans (199). VapA-containing plasmids also encode additional Vap proteins VapC-H (200), while VapB-containing plasmids encode Vap proteins VapI-M (198).…”
Section: Virulence Plasmids In Other Nonsporulating Gram-positive Pamentioning
confidence: 99%